2008
DOI: 10.1016/j.phytochem.2008.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Chlorine-containing iridoid and iridoid glucoside, and other glucosides from leaves of Myoporum bontioides

Abstract: Sixteen compounds were isolated from the MeOH extract of leaves of Myoporum bontioides. The five compounds hitherto unknown, were elucidated to be a chlorine-containing iridoid, named myopochlorin, and an iridoid glucoside, an acylated iridoid glucoside, a linear acetogenin glucoside, and an acyclic monoterpene glucoside, named myobontiosides A-D, respectively, by means of spectroscopic analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 26 publications
0
9
0
2
Order By: Relevance
“…13 C NMR resonances support the identity of the β-d-glucopyranosyl moiety. [20,21] The presence of dglucose in 5 was confirmed by enzymatic hydrolysis with β-glucosidase followed by optical rotation/HPLC analysis. The glycoside 5 could be hydrolyzed by β-glucosidase, which suggests that the sugar is β-d-glucose, because this enzyme has specificity towards β-d-glucose.…”
Section: Resultsmentioning
confidence: 98%
“…13 C NMR resonances support the identity of the β-d-glucopyranosyl moiety. [20,21] The presence of dglucose in 5 was confirmed by enzymatic hydrolysis with β-glucosidase followed by optical rotation/HPLC analysis. The glycoside 5 could be hydrolyzed by β-glucosidase, which suggests that the sugar is β-d-glucose, because this enzyme has specificity towards β-d-glucose.…”
Section: Resultsmentioning
confidence: 98%
“…A reação de acetilação e comparação com dados da literatura 17,18 permitiram a confirmação da proposta estrutural para a referida substância com sua respectiva estereoquímica, que foi identificada como a (1R,5S,6S,7R,8S,9S)-7-cloro-8-(hidroximetil) octa-hidrociclopenta[c]piran-1,10-oxira-5,6,8-triol (miopoclorina), já identificada anteriormente na espécie Myoporum bontioides e que está sendo reportada pela primeira vez em C. biflora, bem como seus derivados acetilados. …”
Section: Resultsunclassified
“…[5] Previous phytochemical studies have revealed some structurally diverse chemicals from this plant, including sesquiterpenoids, iridoids, phenylethanoids, and flavonoids, some of which showed important bioactivities. [6,7] In Vietnam, this species has been found along the coastal regions of the north-eastern. [8] There is no report on the bioactivities and phytochemicals of this plant.…”
Section: Myoporum Bontioides a Gray Belonging To Genusmentioning
confidence: 99%